Intestinal microbiota changes after solid organ transplantation: a systematic review - Carra Forte, Cristina; Forcellini Pedrollo, Elis; Corrêa Souza, Gabriela; Bauermann Leitão, Cristiane (Clinical and Biomedical Research, 2018)
Introduction: The intestinal microbiota may undergo changes after solid organ transplantation. The purpose of this systematic review was to characterize the intestinal microbiota of patients undergoing solid organ transplantation. Methods: MEDLINE, EMBASE and Cochrane Library databases were searched from inception to July 21, 2017. Studies of patients undergoing solid organ transplantation that evaluated changes in intestinal microbiota composition and one of the following outcomes were included: post-transplant weight, new-onset diabetes after transplantation, delayed graft function, acute rejection, graft and patient survival, and post-transplant infections. Results: Out of 765 studies found in this search, two studies (86 patients) fulfilled inclusion criteria. Both studies assessed kidney transplantation recipients, and a reduction in bacterial species diversity after transplantation was observed. Changes in intestinal microbiota were associated with acute rejection in both studies. One study reported diarrhea and urinary infections, while the other one reported urinary and respiratory infections. None of them reported other outcomes of interest. Conclusion: Changes in intestinal microbiota were observed after kidney transplantation, and they were associated with higher incidence of acute rejection and infections in transplant recipients. However, data are still scarce and more studies are needed to evaluate if microbiota changes have an impact on post-transplant outcomes. Keywords: Transplantation; intestinal microbiota; outcomes